Economics : principles and applications - Lieberman, Marc. (South-Western College, 2001)
Preliminaries. Microeconomic decision makers. Product markets. Labor, capital, and financial markets. Efficiency, gornment, and the global economy. Macroeconomics: basic concepts. Long-run macroeconomics. Short-run macroeconomics. Money, Prices, and the macroeconomy. Macroeconomic policy.